Antara Kampus Dan Kekerasan: Mengungkap Pola Sistematik Dalam Kasus Kekerasan Seksual Di Perguruan Tinggi Di Pulau Jawa - Larasati, Ajeng Kristha Sekar; Putri, Maulidia Arifiyani; Asmarani , Puteri (Jurnal Pendidikan Indonesia, 2025)
Violence in higher education institutions in Indonesia has shown an increasing trend, with 82 cases reported (Komnas Perempuan, 2021-2024). This complex phenomenon involves individual (Internal) and systemic (External). factors that create an unsafe academic environment.This study examines the interaction between internal and external factors contributing to sexual violence and evaluates the implementation of policies at six universities on the island of Java. Qualitative descriptive analysis using secondary data (2023-2025) from media reports, policy documents, and academic literature through content analysis. Case studies include UI, UGM, UNDIP, UNAIR, UNPAD, and UNTIRTA. Key findings reveal: 1) Internal factors (Low self-control, moral laxity) interact with external factors (weak oversight, hierarchical structure); 2) Only 33% of cases are reported to the campus task force (PPKS) due to lack of trust; 3) Policy implementation remains inconsistent across institutions. Comprehensive prevention requires: 1) Gender education integrated into the curriculum; 2) A standardized reporting system; 3) Cultural transformation toward an ethical academic environment.